2020
DOI: 10.3390/microorganisms8111804
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Modulates MyD88-Dependent Signaling Pathway in Macrophages during Mycobacterial Infection

Abstract: Recently, we reported that cigarette smoking, and especially nicotine, increases susceptibility to mycobacterial infection and exacerbates inflammation in patients with Crohn’s disease (CD). The macrophagic response to Mycobacterium avium subspecies paratuberculosis (MAP) in CD and Mycobacteria tuberculosis (MTB) continues to be under investigation. The role of toll-like-receptors (TLRs) and cytoplasmic adaptor protein (MyD88) in proinflammatory response during Mycobacterial infection has been suggested. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In TNBS-induced BALB/C mice model of Crohn's disease, nicotine taken twice a day at a total dose of 7.5 mg/kg for 5 days exacerbated colonic inflammation with the appearance of extensive mucosal necrosis in the proximal colon, extensive crypt damage, complete goblet cell depletion, lamina propria destruction, and massive lymphocytic infiltration, which was associated with the inhibition of colonic CD4 T cell nAChRs regulated by IL-12 (40). Nicotine (4 µg/ml) modulated TLR2/ MyD88/IL-8 and exacerbated inflammation in mycobacteria (Mycobacterium avium paratuberculosis)-infected macrophages, providing important insights to understand the effect of nicotine on worsening inflammation symptoms in patients with Crohn's disease (50). Caution should be exercised in nicotine administration due to organ specificity.…”
Section: Pro-inflammatory Effect Of Nicotine On Inflammatory Bowel Di...mentioning
confidence: 99%
“…In TNBS-induced BALB/C mice model of Crohn's disease, nicotine taken twice a day at a total dose of 7.5 mg/kg for 5 days exacerbated colonic inflammation with the appearance of extensive mucosal necrosis in the proximal colon, extensive crypt damage, complete goblet cell depletion, lamina propria destruction, and massive lymphocytic infiltration, which was associated with the inhibition of colonic CD4 T cell nAChRs regulated by IL-12 (40). Nicotine (4 µg/ml) modulated TLR2/ MyD88/IL-8 and exacerbated inflammation in mycobacteria (Mycobacterium avium paratuberculosis)-infected macrophages, providing important insights to understand the effect of nicotine on worsening inflammation symptoms in patients with Crohn's disease (50). Caution should be exercised in nicotine administration due to organ specificity.…”
Section: Pro-inflammatory Effect Of Nicotine On Inflammatory Bowel Di...mentioning
confidence: 99%
“…Taken together, TLR1/2 and TLR2/6 heterodimers may represent a therapeutic target of inhibitory pharmaceuticals to prevent excessive inflammation and viral entry. The recent discovery of MMG11 (a TLR2 inhibitor, which shows preference for the TLR1/2 heterodimer [103,104]) and CuCpt22 (a TLR1/2 heterodimer inhibitor in mice [103] and a TLR1/2/6 inhibitor in humans [103,105]) may represent potential COVID-19 therapeutics. Pre-treatment of MMG11 (5 µg/mL) followed by infection with Mycobacterium avium subspecies paratuberculosis in human macrophages, resulted in significantly reduced concentration of pro-inflammatory cytokines IL-8 and TNFα [104].…”
Section: Tlr1/2/6 As Potential Therapeutic Targets and Alternative Viral Entry Points For Sars-cov-2mentioning
confidence: 99%
“…The recent discovery of MMG11 (a TLR2 inhibitor, which shows preference for the TLR1/2 heterodimer [103,104]) and CuCpt22 (a TLR1/2 heterodimer inhibitor in mice [103] and a TLR1/2/6 inhibitor in humans [103,105]) may represent potential COVID-19 therapeutics. Pre-treatment of MMG11 (5 µg/mL) followed by infection with Mycobacterium avium subspecies paratuberculosis in human macrophages, resulted in significantly reduced concentration of pro-inflammatory cytokines IL-8 and TNFα [104]. Similar anti-inflammatory abilities have been observed in human primary bronchial epithelial cells pre-treated with CuCpt22 (50 µM), 30 min before challenge with Streptococcus pneumonia strain D39 [105].…”
Section: Tlr1/2/6 As Potential Therapeutic Targets and Alternative Viral Entry Points For Sars-cov-2mentioning
confidence: 99%
“…Nicotine also increased NF-ĸB p52 translocation and activation in macrophages in presence or absence of MAP infection ( Table 2 ). This suggests that nicotine activates the antiapoptotic effect of NF-ĸB in MAP-infected macrophages, which may induce several antiapoptotic genes including inhibit caspase-3 activation [ 12 , 26 ]. These results support previous studies that reported that inhibiting NF-ĸB in macrophages leads to increased apoptosis and reduced viability of intracellular MTB [ 24 ].…”
Section: Discussionmentioning
confidence: 99%